2004
DOI: 10.1249/01.mss.0000128185.55587.a3
|View full text |Cite
|
Sign up to set email alerts
|

Strain on the Anterior Cruciate Ligament during Closed Kinetic Chain Exercises

Abstract: The ACL strain responses produced during these CKC exercises were equal and similar to those produced during other rehabilitation exercises (i.e., squatting, active extension of the knee) previously tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
115
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 29 publications
8
115
0
3
Order By: Relevance
“…ACL is a band of fibrous tissue that connects the femur to tibia .Its function is to control the stability of knee when performing twisting or pivoting actions and stops from moving forward (Voss et al 2008) www.jmscr.igmpublication. analyzed ACL injury subjects treated conservatively and ACL -reconstruction, recorded no difference with regard to knee function, health status and return to pre injury level , this study subject conservatively treated with Post ACL injury had similar benefit of improved knee function as per the above reports  Manske et al knee flexion post ACL -reconstruction to be the goal of therapy in 2 months treated conservatively further evidences positively with therapeutic means  Closed kinematic chain exercise were widely used in ACL rehabilitation as they simulate functional activities (Heijne et al 2004) and helps to correct neuromuscular imbalances for optimal biomechanics and reduction of knee injuries (Ford et al 2003). This study subject was treated mainly with close kinematic exercises hence an improved knee functioning was noted…”
Section: Introductionsupporting
confidence: 69%
“…ACL is a band of fibrous tissue that connects the femur to tibia .Its function is to control the stability of knee when performing twisting or pivoting actions and stops from moving forward (Voss et al 2008) www.jmscr.igmpublication. analyzed ACL injury subjects treated conservatively and ACL -reconstruction, recorded no difference with regard to knee function, health status and return to pre injury level , this study subject conservatively treated with Post ACL injury had similar benefit of improved knee function as per the above reports  Manske et al knee flexion post ACL -reconstruction to be the goal of therapy in 2 months treated conservatively further evidences positively with therapeutic means  Closed kinematic chain exercise were widely used in ACL rehabilitation as they simulate functional activities (Heijne et al 2004) and helps to correct neuromuscular imbalances for optimal biomechanics and reduction of knee injuries (Ford et al 2003). This study subject was treated mainly with close kinematic exercises hence an improved knee functioning was noted…”
Section: Introductionsupporting
confidence: 69%
“…Brace condition was treated as a repeated measure, with gender as an independent measure and the horizontal speed of the pelvis as the covariate. Previous research has shown gender may affect knee flexion angle and ground reaction forces [6,11,23,25,28], therefore, gender was included to determine whether there was an interaction effect between brace condition and gender. The goal of this study was to determine the brace effect, and not the gender effect.…”
Section: Methodsmentioning
confidence: 99%
“…After induction of 2% isoflurane inhalation anesthesia, the external fixator was connected to the loading device. The level of graft elongation was chosen on the basis of previous studies that reported 2% to 5% elongation of both the native ACL and ACL grafts in the human knee during light rehabilitation exercises such as pedaling on a stationary bicycle [9][10][11] . Preliminary cadaveric studies confirmed mean normalized graft elongation of 2.2% with use of the loading protocol outlined below.…”
Section: Loading Protocolmentioning
confidence: 99%